Screening for a culture medium yielding optimal colony growth, zoospore yield and infectivity of different isolates of Leptolegnia chapmanii (Straminipila: Peronosporomycetes) - Pelizza, Sebastián Alberto (2011)
Leptolegnia chapmanii is an aquatic fungus that has demonstrated marked pathogenicity towards the larvae of a number of mosquito species with little or no effect on non-target insects. The aim of this work was to determine the best culture medium for colony growth, and production and infectivity of zoospores among different isolates of L. chapmanii. No significant differences (P >0.01) were observed for the media FORT(agar), PYG, YPSS, and PYGSF in terms of colony diameter of the different isolates evaluated. In these culture media, all L. chapmanii isolates had the highest growth (45 mm2) after 7 days. The nine isolates tested produced the greatest number of zoospores in FORT(agar) medium 3 (1 × 106 zoospores/ml). Medium YPSS exhibited significant differences (P <0.0001) compared to other culture media with respect to maintenance of virulence and infectivity of the isolates, producing 100% larval mortality after 48 h of inoculation. Thus, for the cultivation and maintenance of L. chapmanii isolates, the medium of choice among those tested is FORT(agar), as it is both inexpensive to prepare and ensures optimal colony development, extremely high zoospore production, and excellent maintenance of fungal infectivity.